KAJIAN KOMPERATIF LOKASI TUMBUH TERHADAP PROPERTIS BAMBU - Oka, Gusti Made (MEKTEK, 2009)
Bamboo use in civil engineering building has shown increasing demand whetter for in structural or non structural means. On the other hand, bamboo has not been optimally exploted althougth research results have shown that bamboo has strength and better performance compared to other building materials. This research was aimed to reveat the physical and mechanical properties bamboo. Preliminary research was made the physical and mechanical properties specimen bamboo, which following the ISO 1329-1975 standard test method. The result experiment showed that bamboo specific gravity 0,745 gr/cm3 of mainland area and 0,614 gr/cm3 for mountain area. The result experiment showed that bamboo mechanical properties of strength maindland area better mountain area